Fit for print: developing an institutional model of scientific periodical publishing in England, 1665–ca. 1714 - Moxham, N. (Notes Rec R Soc Lond, 2015)
This paper explores the contested afterlife of Philosophical Transactions following the death of its founder, Henry Oldenburg. It investigates the complex interrelation between the institution and the periodical at a time when the latter was supposedly independent, and outlines the competing proposals for institutional publishing in science contemplated in the Royal Society, linking some publications that were actually attempted to those proposals and to the Society's attempts to revitalize its experimental programme between 1677 and 1687. It argues that the Society was concerned to produce experimental natural knowledge over which it could claim ownership, and intended this work for publication in other venues than Transactions, whereas the periodical was seen as a more suitable site for work reported to the Society than for research that the institution had primarily produced. It was only from the early 1690s, after the collapse of the Society's experimental programme, that Transactions gradually became a more straightforward reflection of the mainstream of Royal Society activity, paving the way for its formal reinvention as the official publication of the Society in 1752.